Enhancing soil properties, yield, and corn farmers’ income through crop rotation system (The Philippine Journal of Crop Science, 2018)
In the Philippines, the sustainability of corn production practices is becoming a serious concern as soil degradation intensifies due to continuous corn mono-propping and more frequent torrential rains as a result of climate change. Crop rotation in corn areas with grain legumes e.g. peanut, soybean and mungbean in theory, improve the soil characteristics, decrease pest and disease incidence, and increase farmers’ income. This study shows the advantages of crop rotation compared with continuous corn cropping system in terms of soil fertility and farmers’ income. Yield demonstration plots were planted in three locations across the country (Isabela, Cebu and Bukidnon). The demonstration plots consisted of four treatments; T1 (continuous corn cropping), T2(Corn-mungbean crop rotation), T3 (Corn-soybean crop rotation) and T4 (Corn-peanut crop rotation). In terms of soil properties, the corn-legume crop rotation treatments had higher organic matter content, organic carbon content, soil pH and phosphorus concentration. Treatment 3 (Corn-soybean crop rotation) exhibited the highest improvement in soil characteristics in all followed by treatment 2 (Corn-mungbean crop rotation). In Isabela, T4 (Corn-peanut crop rotation) resulted in the highest cumulative income of Php 292, 581.00 across the four cropping season while the T1(Continuous corn cropping) had the lowest cumulative income of only Php 194, 596.00 while in Cebu and Bukidnon, T2 (Corn- mungbean crop rotation) resulted in the highest cumulative income of Php 225, 040.00 and Php 275, 143.00, respectively. T1 (Continuous corn cropping) gave also the least cumulative income in Cebu and Bukidnon. This study provides local and comprehensive data demonstrating the advantages of corn-legume crop rotation system over continuous corn cropping by enhancing a number of necessary soil characteristics and increasing farmers’ production and income.